2013
DOI: 10.4103/2277-9175.114189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perinatal factors on thyroid stimulating hormone level in cord blood

Abstract: Background:The aim of the present study was to determine the effect of various perinatal factors on cord blood TSH among newborns in Isfahan, Iran.Materials and Methods:This was a descriptive–analytic cross sectional study which performed in Isfahan Iran. During a period of four months, since February to May 2012 a total number of 440 newborns delivered in Alzahra and Shahid beheshti hospitals were enrolled in the study. For all newborns one mL blood sample from umbilical vein was obtained by one of the projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
6
7
0
Order By: Relevance
“…We did not find any significant differences in TSH level according to sex, in line with many previous studies 6 8 12 13 15 21 22) . However, a few studies have reported higher TSH levels in boys 7 14) .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We did not find any significant differences in TSH level according to sex, in line with many previous studies 6 8 12 13 15 21 22) . However, a few studies have reported higher TSH levels in boys 7 14) .…”
Section: Discussionsupporting
confidence: 92%
“…There was no relationship between TSH level and maternal age in our study, in line with most previous studies 6 7 8 12 13) . Only one study has reported a positive relationship between maternal age and TSH level 22) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations